Effect of uniaxial elastic stress on corrosion of X80 pipeline steel in an acidic soil solution containing sulfate-reducing bacteria trapped under disbonded coating. (December 2021) - Wei, Boxin; Xu, Jin; Cheng, Y. Frank; Sun, Cheng; Yu, Changkun; Wang, Zhenyao
Abstract: The effect of elastic stress on corrosion of X80 steel in an acidic soil solution containing sulfate-reducing bacteria (SRB) trapped under a simulated disbonded coating was investigated. The SRB numbers at the coating holiday after 14 days were approximately 10 6 cells/mL, and they were higher than those in the simulated disbonded coating region. The stressed coupons underwent more severe SRB corrosion and pitting at the same locations under the simulated disbonded coating due to the mechanochemical effect. These results indicated that the pitting process was affected by the applied elastic stress in the X80 steel. Highlights: Effect of stress on SRB MIC of X80 steel under disbonded coating was studied. Lack of evidence for stress corrosion mechanism in presence of microorganisms. Stress assisted the SRB MIC behavior of X80 steel under disbonded coating. Both stress effect and film formation affect SRB MIC of X80 steel under disbonded coating.